A educação infantil em Montes Claros: transformações institucionais e processos identitários - Ilma Lemos Pinheiro Lages (2012)
This thesis is part of qualitative research which aimed to understand the construction of the identitary processes of professional Child Education of public institutions from Montes Claros (MG), as well as the senses and meanings attributed by them to the work at that level of education, along their professional trajectories. It was considered that the identity is not a product but a construction and is due to the process of socialization, being constantly constructed and deconstructed by the individual. Conflicts and tensions are part of the biographical trajectories and relational from professionals, leading them to mobilizations and search for professional valorization. The professional identities were studied in an attempt to portray the voice from professionals, pointing the identification processes, the similarities, oppositions and dualities present in this field. The study tried to visualize the transformations political-institutional because it passed over the city in different periods: the first services in nursery at the beginning of the decade of 1980; the passage of the nursery centers in the sector of Assistance for the Education in 1990; the constitution of the Municipal System of Education in 2007; the entrance of the professionals in the different institutions; the conditions of work and the problems faced in relation to the service, to the professional performance, wage and career. This dissertation portrays two dimensions of research: the construction of the history of Child Education in the city and the relation of this history and the current public actions with the construction of professional identities. The research was developed through the documentary analysis and field research in a municipal institution, an institution recently owned and a community institution. As an instrument of data collection were used non-structured interviews and identification forms (professional and personal data) of the researched subjects. For the understanding of the object, he worked with the conception of identity (Dubar, 2005). It was noted that the constitution of the identity from professionals is not made independent of historical structure, political and social. Action and structure it build by themselves mutually. The subject takes part in this process in a dynamic and interactive form. Public policies may not be considered as state policies, but as forms of socialization, where there is interaction of the State with the subject.